Features of the Muscular and Functional Activity of the Tongue in Pediatric Patients with a Distal Bite - Melnyk, А. О.; Kaniura, О. А.; Kopchak, А. В.; Bidenko, Н. В.; Filonenko, В. В. (Actual Dentistry, 2026)
Relevance. Assessing the force of tongue pressure on the surrounding structures of the dentognathic apparatus is an important task for scientists. The forces created by the muscles of the tongue, lips, and cheeks act on the dentition, supporting the shape and stability of the bite. For the purpose of rational diagnosis and orthodontic treatment, it is advisable to establish and consider their correlations. Since the distal bite is the most common dentognathic deformation, it is necessary to investigate the parameters of the tongue’s muscular and functional activity in patients with this pathology. Aim: to assess the distribution of tongue pressure in the surrounding areas of the oral cavity and analyze the relationships between pressure values in different measurement zones to identify functional muscle features of the tongue in pediatric patients with a distal bite. Materials and methods. The subject of the analysis was the results of the examination of 31 patients aged 5 to 12 years with distal bite. Measurement of the tongue pressure force (F, H) in the specified zones of the upper and lower jaws was carried out using the FlexiForce film force sensor. Analog-to-digital conversion of the sensor signal was carried out using an electronic device based on the Arduino Nano microcontroller module and using the SerialSlot software. Results. Analysis of pressure at the moment the patient was advised to press the tongue against the sensor and during swallowing demonstrated significant variability across measurement zones. At the moment when the patients were advised to press the tongue on the sensor, the greatest pressure was noted on the lingual surface of the lower dentition. The obtained topographic distribution of maximum tongue pressure covers the frontal-parasagittal and lateral segments of the lower jaw and may affect occlusal function. The detected increase in pressure along the lingual contour of the lower arch may reflect an adaptive mechanism that redistributes muscle load to stabilize the lower dentition in patients with a distal bite and impaired lingual-dental balance. The significant differences observed in most measurement zones in patients with protrusion or retrusion of the frontal group of teeth, both at the moment when patients were advised to press their tongue on the sensor and during swallowing, may indicate specific kinematics of their movements, with a corresponding potential impact on occlusal function. Conclusions. The distribution of tongue pressure force in children with a distal bite has characteristic features that may be the result of adaptive mechanisms to the changed position of the jaws, which is of great importance for clinical practice, as it can be used for a comprehensive assessment of the orthodontic status of patients and the development of an optimal treatment strategy. This strategy should consider the tongue’s muscle balance, along with other potential etiological factors that can contribute to the development of occlusal disorders.